Stump appendicitis in a 2 year-old patient. Case report and literature review - Andrés Guillermo Ramírez; Fernando Fierro; Diana Alejandra Holguín; Mizrahinn Méndez (Case Reports)
Stump appendicitis is a rare cause of acute abdomen in the pediatric population, therefore, it is not suspected frequently. This paper presents the case report of a 2-year-old child admitted into the emergency room due to vomiting, abdominal pain and fever.